Bipolar type all-solid-state sodium ion secondary battery

The bipolar all-solid-state sodium ion secondary battery addresses energy density and safety issues by using a stacked design with protrusions to prevent short circuits and enhance safety, achieving high voltage without electrolyte leakage or hazardous gas generation.

JP7616253B2Active Publication Date: 2025-01-17NIPPON ELECTRIC GLASS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023007263
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-10-17
Filing Date
2023-01-20
Publication Date
2025-01-17
Estimated Expiration
2038-10-03

AI Technical Summary

Technical Problem

Current lithium-ion secondary batteries face issues with reduced energy density and safety risks due to electrolyte leakage and decomposition, while sulfide-based solid electrolytes pose hazards from hydrogen sulfide generation.

Method used

A bipolar all-solid-state sodium ion secondary battery design with stacked positive and negative electrode layers and a solid electrolyte layer, incorporating protrusions on the current collector and electrolyte layers to prevent short circuits and enhance safety.

Benefits of technology

The design effectively increases voltage without compromising safety by preventing short circuits and reducing gas generation, thus maintaining high energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616253000001
    Figure 0007616253000001
  • Figure 0007616253000002
    Figure 0007616253000002
  • Figure 0007616253000003
    Figure 0007616253000003
Patent Text Reader

Abstract

Provided is a bipolar all-solid-state sodium ion secondary battery that can increase voltage without compromising safety. [Solution] The battery includes a plurality of all-solid-state sodium ion secondary batteries 1, each including a positive electrode layer 3 capable of absorbing and releasing sodium, a solid electrolyte layer 4 made of a sodium ion conductive oxide, and a negative electrode layer 5 capable of absorbing and releasing sodium, stacked in this order; and a current collector layer 2 provided between the positive electrode layer 3 of one of the all-solid-state sodium ion secondary batteries 1 and the negative electrode layer 5 of another of the all-solid-state sodium ion secondary batteries 1, and shared by the positive electrode layer 3 and the negative electrode layer 5. The battery includes a protrusion 6 that is continuous with the outer periphery of the current collector layer 2 in plan view and protrudes outward beyond the outer periphery of the positive electrode layer 3 and / or the negative electrode layer 5, and the thickness of the protrusion 6 is 0.1 μm or more and 15 μm or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a bipolar type all-solid-state sodium ion secondary battery. [Background technology]

[0002] Lithium-ion secondary batteries have established themselves as high-capacity, lightweight power sources essential for mobile devices, electric vehicles, and other applications. However, current lithium-ion secondary batteries primarily use organic electrolytes, resulting in a low voltage of approximately 3.7 V per cell. Therefore, to achieve a higher voltage, multiple cells must be connected in series. However, connecting multiple cells via connectors presents a problem: the electrical resistance of the connectors significantly reduces the voltage. Furthermore, batteries with connectors contain many parts that do not contribute to increasing the voltage, resulting in reduced volumetric and weightwise energy densities (hereinafter collectively referred to as "energy density").

[0003] Bipolar batteries have been proposed as a way to solve this problem. Patent Document 1 below discloses, as an example of a bipolar battery, a lithium secondary battery having a polymer electrolyte layer containing an electrolytic solution. This bipolar battery has a power generating element in which a positive electrode composite layer, a polymer electrolyte layer, and a negative electrode composite layer are stacked in this order. A plurality of power generating elements are connected in series via current collector layers.

[0004] On the other hand, Patent Document 2 below discloses a secondary battery using a sulfide-based solid electrolyte. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Laid-Open No. 2002-075544 [Patent Document 2] Japanese Patent Application Laid-Open No. 2017-147173 Summary of the Invention [Problem to be solved by the invention]

[0006] In bipolar batteries, positive and negative electrodes are repeatedly stacked within a single cell. Therefore, in the bipolar battery described in Patent Document 1, there was a risk of short-circuiting between the positive and negative electrodes due to leakage of the electrolyte from the polymer electrolyte layer. Furthermore, as a result, there was a risk of the electrolyte being exposed to a high voltage of 4.5 V or higher, which is its decomposition potential. This posed a safety issue, as decomposition of the electrolyte within the battery could generate gas, potentially causing the battery to explode and catch fire. Thus, there was a risk of safety being compromised as the voltage of secondary batteries increased.

[0007] On the other hand, when a solid electrolyte is used, as in the secondary battery described in Patent Document 2, fires due to decomposition of the electrolyte solution do not occur. However, sulfide-based solid electrolytes have a safety issue in that they generate hydrogen sulfide and other contaminants when exposed to the atmosphere. Furthermore, sulfide-based solid electrolytes are highly reactive with the atmosphere, making it difficult to isolate the atmosphere in the secondary battery to the extent that hydrogen sulfide and other contaminants are not generated.

[0008] An object of the present invention is to provide a bipolar type all-solid-state sodium ion secondary battery that can increase voltage without compromising safety. [Means for solving the problem]

[0009] The bipolar type all-solid-state sodium ion secondary battery of the present invention is characterized by comprising: a plurality of all-solid-state sodium ion secondary batteries, each having a positive electrode layer capable of absorbing and desorbing sodium, a solid electrolyte layer made of a sodium ion conductive oxide, and a negative electrode layer capable of absorbing and desorbing sodium stacked in this order; and a current collector layer provided between the positive electrode layer of one of the all-solid-state sodium ion secondary batteries and the negative electrode layer of another of the all-solid-state sodium ion secondary batteries, and shared by the positive electrode layer and the negative electrode layer.

[0010] In plan view, it is preferable that a protrusion be provided that is connected to the outer periphery of the current collector layer and protrudes outward from the outer periphery of the positive electrode layer and / or negative electrode layer. In this case, the protrusion may be formed from the same material as the current collector layer. Alternatively, the protrusion may be formed from a material different from that of the current collector layer. In plan view, it is more preferable that the area of ​​the protrusion be 1% or more and 50% or less of the total area of ​​the protrusion and the current collector layer.

[0011] It is preferable that the solid electrolyte layer has a portion that protrudes outward from the outer periphery of the positive electrode layer and / or the negative electrode layer in a plan view. In this case, it is more preferable that the area of ​​the portion of the solid electrolyte layer that protrudes outward from the outer periphery of the positive electrode layer and / or the negative electrode layer in a plan view is 1% or more and 50% or less of the area of ​​the solid electrolyte layer.

[0012] The current collector layer may be made of at least one material selected from the group consisting of aluminum, titanium, silver, copper, stainless steel, alloys containing these metals, and graphite.

[0013] The solid electrolyte layer preferably contains at least one of β-alumina, β″-alumina, and NASICON-type crystals. [Effects of the Invention]

[0014] According to the present invention, it is possible to provide a bipolar type all-solid-state sodium ion secondary battery that can increase voltage without compromising safety. [Brief explanation of the drawings]

[0015] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a bipolar-type all-solid-state sodium ion secondary battery according to a first embodiment of the present invention. [Figure 2] FIG. 2 is a schematic plan view seen from the positive electrode layer side, showing a portion where two all-solid-state sodium ion secondary batteries are connected via a current collector layer in the bipolar all-solid-state sodium ion secondary battery according to the first embodiment of the present invention. [Figure 3] FIG. 3 is a schematic plan view showing the all-solid-state sodium ion secondary battery according to the first embodiment of the present invention, viewed from the positive electrode layer side. [Figure 4] FIG. 4 is a schematic cross-sectional view illustrating a state in which Na dendrites are precipitated from the negative electrode layer in the first embodiment of the present invention. [Figure 5] FIG. 5 is a schematic cross-sectional view showing a bipolar type all-solid-state sodium ion secondary battery according to a first modified example of the first embodiment of the present invention. [Figure 6] FIG. 6 is a schematic cross-sectional view showing a bipolar type all-solid-state sodium ion secondary battery according to a second modified example of the first embodiment of the present invention. [Figure 7] FIG. 7 is a schematic cross-sectional view showing a bipolar type all-solid-state sodium ion secondary battery according to a third modified example of the first embodiment of the present invention. [Figure 8] FIG. 8 is a schematic cross-sectional view showing a bipolar type all-solid-state sodium ion secondary battery according to a fourth modified example of the first embodiment of the present invention. [Figure 9] FIG. 9 is a schematic cross-sectional view showing a bipolar type all-solid-state sodium ion secondary battery according to a fifth modified example of the first embodiment of the present invention. [Figure 10] FIG. 10 is a schematic cross-sectional view showing a bipolar type all-solid-state sodium ion secondary battery according to a sixth modified example of the first embodiment of the present invention. [Figure 11] FIG. 11 is a schematic cross-sectional view showing the bipolar-type all-solid-state sodium ion secondary battery of Example 1. [Figure 12] FIG. 12 is a diagram showing charge / discharge curves of the test battery of Comparative Example 1. [Figure 13] FIG. 13 is a diagram showing the charge / discharge curves of the evaluation battery of Example 1. [Figure 14] FIG. 14 is a diagram showing charge / discharge curves of the evaluation batteries of Example 2, Example 3, and Comparative Example 2. DETAILED DESCRIPTION OF THE INVENTION

[0016] Preferred embodiments will be described below. However, the following embodiments are merely examples, and the present invention is not limited to the following embodiments. In addition, in each drawing, components having substantially the same functions may be referred to by the same reference numerals.

[0017] (First embodiment) Fig. 1 is a schematic cross-sectional view showing a bipolar type all-solid-state sodium ion secondary battery according to a first embodiment of the present invention. As shown in Fig. 1, a bipolar type all-solid-state sodium ion secondary battery 10 according to this embodiment includes a plurality of all-solid-state sodium ion secondary batteries 1, and further includes a current collector layer 2 provided between the plurality of all-solid-state sodium ion secondary batteries 1. The plurality of all-solid-state sodium ion secondary batteries 1 are connected in series via the current collector layer 2. The number of all-solid-state sodium ion secondary batteries 1 in the bipolar type all-solid-state sodium ion secondary battery 10 is not limited to two, and may be three or more.

[0018] In the all-solid-state sodium ion secondary battery 1, a positive electrode layer 3 capable of absorbing and desorbing sodium, a solid electrolyte layer 4 made of a sodium ion conductive oxide, and a negative electrode layer 5 also capable of absorbing and desorbing sodium are laminated in this order. Of a plurality of all-solid-state sodium ion secondary batteries 1 adjacent to each other with a current collector layer 2 interposed therebetween, the positive electrode layer 3 of one all-solid-state sodium ion secondary battery 1 and the negative electrode layer 5 of the other all-solid-state sodium ion secondary battery 1 share the current collector layer 2.

[0019] The current collector layer 2 has a first main surface 2a located on the positive electrode layer 3 side and a second main surface 2b located on the negative electrode layer 5 side. The solid electrolyte layer 4 has a third main surface 4a located on the positive electrode layer 3 side and a fourth main surface 4b located on the negative electrode layer 5 side.

[0020] The current collector layer 2 is made of, but is not particularly limited to, at least one material selected from the group consisting of aluminum, titanium, silver, copper, stainless steel, alloys containing these metals, and graphite. In this embodiment, the current collector layer 2 is made of aluminum. The thickness of the current collector layer 2 is, but is not particularly limited to, 3 μm in this embodiment.

[0021] A first metal film 7 for current collection is provided on the positive electrode layer 3 located outermost in the stacking direction of the all-solid-state sodium ion secondary battery 1 of the bipolar type all-solid-state sodium ion secondary battery 10. A second metal film 8 for current collection is provided on the negative electrode layer 5 located outermost in the stacking direction. The first metal film 7 and the second metal film 8 can be made of the same material as the current collector layer 2. Note that the first metal film 7 and the second metal film 8 do not necessarily have to be provided. However, by having the first metal film 7 and the second metal film 8, current can be collected efficiently.

[0022] 2 is a schematic plan view seen from the positive electrode layer 3 side, showing a portion in the bipolar all-solid-state sodium ion secondary battery according to the first embodiment of the present invention where two all-solid-state sodium ion secondary batteries are connected via a current collector layer 2. Note that in FIG. 2, the solid electrolyte layer and the like are omitted.

[0023] As shown in FIG. 2 , the current collector layer 2 has a protrusion 6 that is connected to the entire outer periphery thereof in plan view and that protrudes outward beyond the outer peripheries of the positive electrode layer 3 and the negative electrode layer 5. The protrusion 6 may protrude outward beyond at least a portion of the outer periphery of the positive electrode layer 3 and / or the negative electrode layer 5 in plan view. The protrusion 6 may be connected to at least a portion of the outer periphery of the current collector layer 2. In this embodiment, the current collector layer 2 and the protrusion 6 are integrally formed from the same material. The thickness of the protrusion 6 is 3 μm, the same as that of the current collector layer 2. The bipolar all-solid-state sodium ion secondary battery 10 does not necessarily have to have the protrusion 6.

[0024] 3 is a schematic plan view showing the all-solid-state sodium-ion secondary battery according to the first embodiment of the present invention, as viewed from the side of the positive electrode layer 3. As shown in FIG. 3, the solid electrolyte layer 4 has a solid electrolyte layer protrusion 9 that is a portion that protrudes outward from the outer peripheries of the positive electrode layer 3 and the negative electrode layer 5 in plan view. Note that the solid electrolyte layer protrusion 9 only needs to protrude outward from at least a portion of the outer periphery of the positive electrode layer 3 and / or the negative electrode layer 5 in plan view. Note that the solid electrolyte layer 4 does not necessarily have to have the solid electrolyte layer protrusion 9.

[0025] A feature of this embodiment is that a plurality of all-solid-state sodium ion secondary batteries 1 are connected in series via the current collector layers 2. This makes it possible to effectively increase the voltage. The all-solid-state sodium ion secondary battery 1 uses a solid electrolyte layer 4 made of a sodium ion conductive oxide, so that the above-mentioned fire caused by decomposition of the electrolyte solution and the generation of harmful gases due to reaction with the atmosphere are unlikely to occur. Therefore, the voltage can be effectively increased without compromising safety.

[0026] In the all-solid-state sodium-ion secondary battery 1, Na dendrites, which are needle-shaped crystals of Na, may precipitate in the anode layer 5 during charging. Repeated charge and discharge may cause the Na dendrites to grow. When Na dendrites precipitate, they are likely to precipitate from the side surface of the anode layer 5 that is not in contact with the current collector layer 2 and the solid electrolyte layer 4. If Na dendrites grow, they may come into contact with the cathode layer 3, causing a short circuit. In contrast, in this embodiment, even if Na dendrites grow, a short circuit between the anode layer 5 and the cathode layer 3 is unlikely to occur. This will be explained with reference to FIG. 4 below.

[0027] FIG. 4 is a schematic cross-sectional view illustrating a state in which Na dendrites are precipitated from the negative electrode layer in the first embodiment of the present invention.

[0028] As shown in FIG. 4 , the bipolar all-solid-state sodium ion secondary battery 10 has a protrusion 6 that protrudes outward from the outer periphery of the negative electrode layer 5 in a plan view. Therefore, even if Na dendrites A grow and progress toward the positive electrode layer 3 of another all-solid-state sodium ion secondary battery 1 connected to the negative electrode layer 5 via the current collector layer 2, the progress of the Na dendrites A is blocked by the protrusion 6. This makes it difficult for short circuits to occur between the all-solid-state sodium ion secondary batteries 1. In addition, the protrusion 6 protrudes outward from the outer periphery of the positive electrode layer 3 in a plan view. Therefore, even if Na dendrites A overcome the protrusion 6, the distance that Na dendrites A must travel to reach the positive electrode layer 3 from the negative electrode layer 5 becomes longer. This makes it even more difficult for short circuits to occur between the all-solid-state sodium ion secondary batteries 1.

[0029] Furthermore, in this embodiment, the solid electrolyte layer 4 has a solid electrolyte layer protrusion 9 that protrudes outward from the outer periphery of the anode layer 5 in a plan view. Therefore, even if Na dendrite A advances toward the cathode layer 3 in the all-solid-state sodium ion secondary battery 1, the solid electrolyte layer protrusion 9 inhibits the advance of Na dendrite A. Therefore, a short circuit between the anode layer 5 and the cathode layer 3 in the all-solid-state sodium ion secondary battery 1 is unlikely to occur. In addition, the solid electrolyte layer protrusion 9 protrudes outward from the outer periphery of the cathode layer 3 in a plan view. Therefore, even if Na dendrite A overcomes the protrusion 6, the distance that Na dendrite A must travel to reach the anode layer 5 from the cathode layer 3 becomes longer. Therefore, a short circuit is even less likely to occur in the all-solid-state sodium ion secondary battery 1.

[0030] In a plan view from the first main surface 2a of the current collector layer 2, the area of ​​the protrusions 6 is preferably 1% or more, 3% or more, and particularly 10% or more of the total area of ​​the protrusions 6 and the current collector layer 2. In this case, the distance that Na dendrites A must travel to reach the negative electrode layer 5 from the positive electrode layer 3 can be increased. This makes it even more difficult for the negative electrode layer 5 and the positive electrode layer 3 to short-circuit. In a plan view from the second main surface 2b of the current collector layer 2, the area of ​​the protrusions 6 is preferably 1% or more, 5% or more, and particularly 15% or more of the total area of ​​the protrusions 6 and the current collector layer 2. This makes it even more difficult for the Na dendrites A to advance. This makes it even more difficult for the negative electrode layer 5 and the positive electrode layer 3 to short-circuit.

[0031] In a plan view from the first main surface 2a side of the current collector layer 2, the area of ​​the protrusions 6 is preferably 50% or less, 40% or less, and particularly 35% or less of the total area of ​​the protrusions 6 and the current collector layer 2. In a plan view from the second main surface 2b side of the current collector layer 2, the area of ​​the protrusions 6 is preferably 50% or less, 40% or less, and particularly 35% or less of the total area of ​​the protrusions 6 and the current collector layer 2. If the above area ratio is too large, it may be difficult to reduce the size of the bipolar all-solid-state sodium ion secondary battery 10.

[0032] In a plan view from the third main surface 4a side of the solid electrolyte layer 4, the area of ​​the solid electrolyte layer protrusion 9 is preferably 1% or more, 3% or more, and particularly 10% or more of the area of ​​the solid electrolyte layer 4. In this case, the distance that the Na dendrite A must travel to reach the negative electrode layer 5 and the positive electrode layer 3 can be increased. This makes it even more difficult for the negative electrode layer 5 and the positive electrode layer 3 to short-circuit. In a plan view from the fourth main surface 4b side of the solid electrolyte layer 4, the area of ​​the solid electrolyte layer protrusion 9 is preferably 1% or more, 5% or more, and particularly 15% or more of the area of ​​the solid electrolyte layer 4. This makes it possible to effectively inhibit the progression of the Na dendrite A. This makes it even more difficult for the negative electrode layer 5 and the positive electrode layer 3 to short-circuit.

[0033] In a plan view from the third main surface 4a side of the solid electrolyte layer 4, the area of ​​the solid electrolyte layer protrusion 9 is preferably 50% or less, 40% or less, and particularly 35% or less of the area of ​​the solid electrolyte layer 4. If this area ratio is too large, the area of ​​the positive electrode layer 3 will be small, and there is a risk that the charge / discharge capacity will not be sufficiently large. In a plan view from the fourth main surface 4b side of the solid electrolyte layer 4, the area of ​​the solid electrolyte layer protrusion 9 is preferably 50% or less, 40% or less, and particularly 35% or less of the area of ​​the solid electrolyte layer 4. If this area ratio is too large, the area of ​​the negative electrode layer 5 will be small, and there is a risk that the charge / discharge capacity will not be sufficiently large.

[0034] The thickness of the current collector layer 2 is preferably 0.1 μm or more, and more preferably 3 μm or more. By setting the thickness of the current collector layer 2 within the above range, it is possible to suppress short-circuiting between the positive electrode layer 3 and the negative electrode layer 5 that are adjacent to each other via the current collector layer 2. The thickness of the current collector layer 2 is preferably 50 μm or less, and more preferably 15 μm or less. If the current collector layer 2 is too thick, the energy density of the bipolar all-solid-state sodium ion secondary battery 10 tends to decrease.

[0035] The thickness of the protrusions 6 is preferably 0.1 μm or more, and more preferably 3 μm or more. By setting the thickness of the protrusions 6 within the above range, the protrusions 6 are less likely to be damaged by Na dendrites A, and the negative electrode layer 5 and the positive electrode layer 3 are even less likely to short-circuit. The thickness of the protrusions 6 is preferably 50 μm or less, and more preferably 15 μm or less. If the protrusions 6 are too thick, the energy density of the bipolar all-solid-state sodium ion secondary battery 10 tends to decrease.

[0036] The following describes first to sixth modified examples of the first embodiment. In the first to sixth modified examples, as in the first embodiment, the voltage can be increased without compromising safety, and short circuits are less likely to occur.

[0037] 5 is a schematic cross-sectional view showing a bipolar all-solid-state sodium ion secondary battery according to a first modification of the first embodiment of the present invention. In this modification, a first metal film 27 is provided between the positive electrode layer 3 and the current collector layer 2, and a second metal film 28 is provided between the negative electrode layer 5 and the current collector layer 2.

[0038] The thickness of the first metal film 27 is preferably thinner than the thickness of the current collector layer 2. This makes it easier to conform the surface shape of the first metal film 27 to the surface shape of the positive electrode layer 3, thereby improving adhesion between the first metal film 27 and the positive electrode layer 3. Similarly, the thickness of the second metal film 28 is preferably thinner than the thickness of the current collector layer 2, which improves adhesion between the second metal film 28 and the negative electrode layer 5. This effectively improves current collection efficiency. The first metal film 27 and the second metal film 28 can be made of the same material as the current collector layer 2. The first metal film 27 and the second metal film 28 can be formed by, for example, sputtering or vacuum deposition.

[0039] 6 is a schematic cross-sectional view showing a bipolar all-solid-state sodium ion secondary battery according to a second modification of the first embodiment of the present invention. In this modification, the solid electrolyte layer protrusion 39 of the solid electrolyte layer 34 protrudes outward only from the outer peripheral edge of the positive electrode layer 3 in plan view.

[0040] 7 is a schematic cross-sectional view showing a bipolar all-solid-state sodium ion secondary battery according to a third modification of the first embodiment of the present invention, in which the solid electrolyte layer 44 does not have a solid electrolyte layer protrusion.

[0041] 8 is a schematic cross-sectional view showing a bipolar all-solid-state sodium ion secondary battery according to a fourth modification of the first embodiment of the present invention. In this modification, protrusion 56 and solid electrolyte layer protrusion 59 of solid electrolyte layer 54 protrude outward only from the outer periphery of negative electrode layer 5 in plan view.

[0042] 9 is a schematic cross-sectional view showing a bipolar all-solid-state sodium ion secondary battery according to a fifth modified example of the first embodiment of the present invention. In this modified example, no protrusion is provided that continues to the outer periphery of the current collector layer 2.

[0043] 10 is a schematic cross-sectional view showing a bipolar all-solid-state sodium ion secondary battery according to a sixth modified example of the first embodiment of the present invention. In this modified example, the current collector layer 2 and the protrusions 66 are made of different materials. The protrusions 66 may be made of an appropriate metal, or may be made of an appropriate resin, ceramics, or the like.

[0044] The solid electrolyte layer 4, the positive electrode layer 3, and the negative electrode layer 5 used in the bipolar all-solid-state sodium ion secondary battery 10 of this embodiment will be described in detail below.

[0045] (Solid electrolyte layer) In this embodiment, the solid electrolyte layer 4 is formed of a sodium ion conductive oxide. Examples of sodium ion conductive oxides include compounds containing at least one selected from Al, Y, Zr, Si, and P, Na, and O, and specific examples thereof include β-alumina, β"-alumina, and NASICON-type crystals. These are preferably used because of their excellent sodium ion conductivity.

[0046] Examples of oxide materials containing β-alumina or β"-alumina include those containing, in mole percent, 65% to 98% Al2O3, 2% to 20% Na2O, and 0.3% to 15% MgO and Li2O. The reasons for limiting the composition in this way are explained below. In the following explanation, unless otherwise specified, "%" means "mol %." Furthermore, "○ + ○ +···" means the total amount of the corresponding components.

[0047] Al2O3 is the main component constituting β-alumina and β"-alumina. The Al2O3 content is preferably 65% ​​to 98%, particularly 70% to 95%. If the Al2O3 content is too low, the ionic conductivity tends to decrease. On the other hand, if the Al2O3 content is too high, α-alumina, which does not have ion conductivity, remains, and the ionic conductivity tends to decrease.

[0048] Na2O is a component that imparts sodium ion conductivity to the solid electrolyte layer 4. The Na2O content is preferably 2% to 20%, 3% to 18%, and particularly preferably 4% to 16%. If the Na2O content is too low, it becomes difficult to obtain the above effects. On the other hand, if the Na2O content is too high, the excess sodium forms compounds such as NaAlO2 that do not contribute to ion conductivity, which tends to reduce ion conductivity.

[0049] MgO and Li2O are components (stabilizers) that stabilize the structures of β-alumina and β"-alumina. The content of MgO + Li2O is preferably 0.3% to 15%, 0.5% to 10%, and particularly preferably 0.8% to 8%. If the amount of MgO + Li2O is too small, α-alumina will remain in the solid electrolyte layer 4, which will likely reduce ionic conductivity. On the other hand, if the amount of MgO + Li2O is too large, MgO or Li2O that did not function as a stabilizer will remain in the solid electrolyte layer 4, which will likely reduce ionic conductivity.

[0050] In addition to the above components, the solid electrolyte layer 4 preferably contains ZrO2 and Y2O3. ZrO2 and Y2O3 have the effect of suppressing abnormal grain growth of β-alumina and / or β"-alumina when the raw materials are fired to produce the solid electrolyte layer 4, and improving the adhesion between the particles of β-alumina and / or β"-alumina. The ZrO2 content is preferably 0% to 15%, 1% to 13%, and particularly 2% to 10%. The Y2O3 content is preferably 0% to 5%, 0.01% to 4%, and particularly 0.02% to 3%. If the amount of ZrO2 or Y2O3 is too large, the amount of β-alumina and / or β"-alumina produced decreases, and ionic conductivity is likely to decrease.

[0051] NASICON type crystals include those of the general formula Na s A1 t A2 u O v (A1 is at least one selected from Al, Y, Yb, Nd, Nb, Ti, Hf and Zr, A2 is at least one selected from Si and P, s = 1.4 to 5.2, t = 1 to 2.9, u = 2.8 to 4.1, v = 9 to 14). A preferred form of the above crystal is where A1 is at least one selected from Y, Nb, Ti and Zr, s = 2.5 to 3.5, t = 1 to 2.5, u = 2.8 to 4, v = 9.5 to 12. By doing so, a crystal with excellent ionic conductivity can be obtained. In particular, a monoclinic or trigonal NASICON-type crystal is preferred because of its excellent ionic conductivity.

[0052] The above general formula Na s A1 t A2 u O v A specific example of the crystal represented by the formula is Na3Zr2Si2PO 12 , Na 3.2 Zr 1.3 Si 2.2 P 0.8 O 10.5 , Na3Zr 1.6 Ti 0.4 SiPO 12 , Na3Hf2Si2PO 12 , Na 3.4 Zr 0.9 Hf 1.4 Al 0.6 Si 1.2 P 1.8 O 12 , Na3Zr 1.7 Nb 0.24 SiPO 12 , Na 3.6 Ti 0.2 Y 0.8 Si 2.8 O9, Na3Zr 1.88 Y 0.12 SiPO 12 , Na 3.12 Zr 1.88 Y 0.12 SiPO 12 , Na 3.6Zr 0.13 Yb 1.67 Si 0.11 P 2.9 O 12 etc.

[0053] The thickness of the solid electrolyte layer 4 is preferably in the range of 10 μm to 2000 μm, and more preferably in the range of 50 μm to 200 μm. If the thickness of the solid electrolyte layer 4 is too thin, the mechanical strength decreases and the layer is more susceptible to breakage. Also, an internal short circuit is more likely to occur. If the thickness of the solid electrolyte layer 4 is too thick, the ion conduction distance during charge and discharge increases, resulting in increased internal resistance and a tendency for the discharge capacity and operating voltage to decrease. Furthermore, the energy density of the bipolar all-solid-state sodium ion secondary battery 10 also tends to decrease.

[0054] The solid electrolyte layer 4 can be produced by mixing raw material powders, molding the mixed raw material powders, and then firing the molded product. For example, the solid electrolyte layer 4 can be produced by forming a green sheet from the raw material powders into a slurry, and then firing the green sheet. Alternatively, the solid electrolyte layer 4 may be produced by a sol-gel method.

[0055] (positive electrode layer) The positive electrode layer 3 in this embodiment is not particularly limited as long as it contains a positive electrode active material capable of absorbing and releasing sodium and functions as the positive electrode layer 3. For example, it may be formed by firing an active material precursor powder such as glass powder. By firing the active material precursor powder, active material crystals are precipitated, and these active material crystals act as the positive electrode active material.

[0056] Examples of active material crystals that function as positive electrode active materials include sodium transition metal phosphate crystals containing Na, M (M is at least one transition metal element selected from Cr, Fe, Mn, Co, V, and Ni), P, and O. Specific examples include Na2FeP2O7, NaFePO4, Na3V2(PO4)3, Na2NiP2O7, Na 3.64 Ni 2.18 (P2O7)2, Na3Ni3(PO4)2(P2O7), Na2CoP2O7, Na 3.64 Co 2.18(P2O7)2, etc. The sodium transition metal phosphate crystal is preferred because it has a high capacity and excellent chemical stability. Among them, triclinic crystals belonging to the space group P1 or P-1, especially those of the general formula Na x M y P2O z A crystal represented by the formula (1.2≦x≦2.8, 0.95≦y≦1.6, 6.5≦z≦8) is preferred because it has excellent cycle characteristics. Other active material crystals that act as positive electrode active materials include NaCrO2, Na 0.7 MnO2, NaFe 0.2 Mn 0.4 Ni 0.4 Examples of such crystals include layered sodium transition metal oxide crystals such as O. The positive electrode active material crystals contained in the positive electrode layer may be a single phase in which only one type of crystal is precipitated, or a mixed phase in which multiple types of crystals are precipitated.

[0057] Examples of active material precursor powders include those containing (i) at least one transition metal element selected from Cr, Fe, Mn, Co, Ni, Ti, and Nb, (ii) at least one element selected from P, Si, and B, and (iii) O.

[0058] The positive electrode active material precursor powder includes, in particular, at least one of phosphate, silicate, and borate, capable of absorbing and releasing sodium, specifically, those containing, in mole percent oxide equivalent, 8% to 55% Na2O, 10% to 70% CrO+FeO+MnO+CoO+NiO, and 15% to 70% PO5+SiO2+BO3. The reasons for limiting each component in this way are explained below. In the following description of the content of each component, "%" means "mol %" unless otherwise specified.

[0059] Na2O serves as a source of sodium ions that migrate between the positive electrode active material and the negative electrode active material during charge and discharge. The Na2O content is preferably 8% to 55%, 15% to 45%, and particularly 25% to 35%. If the Na2O content is too low, fewer sodium ions contribute to absorption and desorption, which tends to reduce the discharge capacity. On the other hand, if the Na2O content is too high, foreign crystals such as Na3PO4 that do not contribute to charge and discharge are more likely to precipitate, which tends to reduce the discharge capacity.

[0060] CrO, FeO, MnO, CoO, and NiO are components that act as a driving force for the absorption and release of sodium ions by changing the valence of each transition element during charge and discharge, causing a redox reaction. NiO and MnO, in particular, are effective in increasing the redox potential. FeO is particularly effective in stabilizing the structure during charge and discharge, improving cycle performance. The content of CrO+FeO+MnO+CoO+NiO is preferably 10% to 70%, 15% to 60%, 20% to 55%, 23% to 50%, 25% to 40%, and particularly 26% to 36%. If the amount of CrO+FeO+MnO+CoO+NiO is too low, the redox reaction associated with charge and discharge is less likely to occur, resulting in fewer absorbed and released sodium ions, which tends to reduce the discharge capacity. On the other hand, if the amount of CrO+FeO+MnO+CoO+NiO is too high, heterogeneous crystals tend to precipitate, reducing the discharge capacity.

[0061] P2O5, SiO2, and B2O3 form a three-dimensional network structure, which has the effect of stabilizing the structure of the positive electrode active material. P2O5 and SiO2 are particularly preferred due to their excellent ionic conductivity, with P2O5 being the most preferred. The content of P2O5 + SiO2 + B2O3 is 15% to 70%, preferably 20% to 60%, and especially 25% to 45%. If the content of P2O5 + SiO2 + B2O3 is too low, the discharge capacity tends to decrease after repeated charge and discharge. On the other hand, if the content of P2O5 + SiO2 + B2O3 is too high, heterogeneous crystals such as P2O5 that do not contribute to charge and discharge tend to precipitate. The contents of P2O5, SiO2, and B2O3 are preferably 0% to 70%, 15% to 70%, 20% to 60%, and especially 25% to 45%, respectively.

[0062] Furthermore, vitrification can be facilitated by incorporating various other components in addition to the above components, provided that the effect as a positive electrode active material is not impaired. Examples of such components include, in oxide notation, MgO, CaO, SrO, BaO, ZnO, CuO, Al2O3, GeO2, Nb2O5, TiO2, ZrO2, V2O5, and Sb2O5. Al2O3, which functions as a network-forming oxide, and V2O5, which serves as an active material component, are particularly preferred. The total content of the above components is preferably 0% to 30%, 0.1% to 20%, and particularly preferably 0.5% to 10%.

[0063] The positive electrode active material precursor powder is preferably one that, upon firing, forms an amorphous phase together with the positive electrode active material crystals. The formation of the amorphous phase improves sodium ion conductivity in the positive electrode layer 3 and at the interface between the positive electrode layer 3 and the solid electrolyte layer 4.

[0064] The average particle size of the active material precursor powder is preferably 0.01 μm to 15 μm, 0.05 μm to 12 μm, and particularly preferably 0.1 μm to 10 μm. If the average particle size of the active material precursor powder is too small, the cohesion between the active material precursor powder particles will be strong, and dispersibility will tend to be poor when the powder is made into a paste. As a result, the internal resistance of the battery will increase and the operating voltage will tend to decrease. In addition, the electrode density will decrease, and the capacity per unit volume of the battery will tend to decrease. On the other hand, if the average particle size of the active material precursor powder is too large, sodium ions will be less likely to diffuse and the internal resistance will tend to increase. In addition, the surface smoothness of the electrode will tend to be poor.

[0065] In the present invention, the average particle size means D50 (volume-based average particle size) and indicates a value measured by a laser diffraction scattering method.

[0066] The thickness of the positive electrode layer 3 is preferably in the range of 3 μm to 300 μm, and more preferably in the range of 10 μm to 150 μm. If the thickness of the positive electrode layer 3 is too thin, the capacity of the bipolar all-solid-state sodium ion secondary battery 10 itself will be small, and the energy density will tend to decrease. If the thickness of the positive electrode layer 3 is too thick, the resistance to electronic conduction will be large, and the discharge capacity and operating voltage will tend to decrease.

[0067] The positive electrode layer 3 may contain a solid electrolyte powder as needed. The solid electrolyte powder may be a powder of the same material as that of the solid electrolyte layer 4. The inclusion of the solid electrolyte powder can improve sodium ion conductivity within the positive electrode layer 3 and at the interface between the positive electrode layer 3 and the solid electrolyte layer 4. The average particle diameter of the solid electrolyte powder is preferably 0.01 μm to 15 μm, more preferably 0.05 μm to 10 μm, and even more preferably 0.1 μm to 5 μm. If the average particle diameter of the solid electrolyte powder is too large, the distance required for sodium ion conduction tends to increase, resulting in a decrease in sodium ion conductivity. Furthermore, the sodium ion conduction path between the positive electrode active material powder and the solid electrolyte powder tends to decrease. As a result, the discharge capacity tends to decrease. On the other hand, if the average particle diameter of the solid electrolyte powder is too small, degradation due to elution of sodium ions or reaction with carbon dioxide gas occurs, resulting in a decrease in sodium ion conductivity. Furthermore, voids tend to be formed, resulting in a decrease in electrode density. As a result, the discharge capacity tends to decrease.

[0068] The volume ratio of the active material precursor powder to the solid electrolyte powder is preferably 20:80 to 95:5, 30:70 to 90:10, and particularly preferably 35:65 to 88:12.

[0069] Furthermore, the positive electrode layer 3 may contain a conductive additive such as carbon powder, if necessary. The inclusion of the conductive additive can reduce the internal resistance of the positive electrode layer 3. The conductive additive is preferably contained in the positive electrode layer 3 in an amount of 0 to 20% by mass, and more preferably in an amount of 1 to 10% by mass.

[0070] (negative electrode layer) The negative electrode layer 5 is not particularly limited as long as it contains a negative electrode active material capable of absorbing and releasing sodium and functions as a negative electrode layer. The negative electrode active material may be formed, for example, by firing a negative electrode active material precursor powder such as glass powder. By firing the negative electrode active material precursor powder, negative electrode active material crystals are precipitated, and these negative electrode active material crystals act as the negative electrode active material.

[0071] Examples of negative electrode active material crystals that act as negative electrode active materials include crystals containing at least one selected from Nb and Ti and O, metal crystals of at least one selected from Sn, Bi, and Sb, and alloy crystals containing at least one selected from Sn, Bi, and Sb.

[0072] Crystals containing O and at least one selected from Nb and Ti are preferred because they have excellent cycle characteristics. Furthermore, if the crystals containing O and at least one selected from Nb and Ti also contain Na and / or Li, the charge / discharge efficiency (ratio of discharge capacity to charge capacity) increases, and a high charge / discharge capacity can be maintained, which is preferable. Among these, if the crystals containing O and at least one selected from Nb and Ti are orthorhombic crystals, hexagonal crystals, cubic crystals, or monoclinic crystals, particularly monoclinic crystals belonging to the space group P21 / m, they are more preferable because they are less likely to experience a decrease in capacity even when charged and discharged at a large current.

[0073] Examples of orthorhombic crystals include NaTiO. Examples of hexagonal crystals include NaTiO and NaTiO. 13 , NaTiO2, LiNbO3, LiNbO2, Li7NbO6, Li2Ti3O7, etc. Cubic crystals include Na2TiO3, NaNbO3, Li4Ti5O 12 , Li3NbO4, etc. Examples of monoclinic crystals include Na2Ti6O 13 , NaTi2O4, Na2TiO3, Na4Ti5O 12 , Na2Ti4O9, Na2Ti9O 19 , Na2Ti3O7, Li 1.7 Nb2O5, Li 1.9 Nb2O5, Li 12 Nb 13 O 33 , LiNb3O8, etc. Examples of monoclinic crystals belonging to the space group P21 / m include Na2Ti3O7, etc.

[0074] The crystal containing at least one selected from Nb and Ti and O preferably further contains at least one selected from B, Si, P, and Ge. These components facilitate the formation of an amorphous phase together with the negative electrode active material crystal, and have the effect of further improving sodium ion conductivity.

[0075] Other examples that can be used include Na metal crystals, alloy crystals containing at least Na (e.g., Na-Sn alloys, Na-In alloys), metal crystals of at least one type selected from Sn, Bi, and Sb, alloy crystals containing at least one type selected from Sn, Bi, and Sb (e.g., Sn-Cu alloys, Bi-Cu alloys, Bi-Zn alloys), and glasses containing at least one type selected from Sn, Bi, and Sb. These are preferred because they have high capacity and are less likely to decrease in capacity even when charged and discharged at a large current.

[0076] The negative electrode active material precursor powder preferably contains at least one of phosphate, silicate, and borate, capable of absorbing and releasing sodium. Specifically, the powder preferably contains, in mole percent oxide equivalent, 0% to 90% SnO, 30% to 90% BiO, 20% to 90% TiO, 30% to 90% FeO, 50% to 90% NbO, 55% to 75% SiO + BO + PO, and 0% to 80% NaO. This composition allows for the formation of a structure in which the negative electrode active material components, Sn ions, Bi ions, Ti ions, Fe ions, or Nb ions, are more uniformly dispersed in an oxide matrix containing Si, B, or P. Furthermore, the inclusion of NaO results in a material with even better sodium ion conductivity. As a result, volumetric changes during absorbing and releasing sodium ions can be suppressed, enabling the production of a negative electrode active material with even better cycle characteristics.

[0077] The reasons for limiting the composition of the negative electrode active material precursor powder as described above are explained below. In the following explanation, unless otherwise specified, "%" means "mol %." Furthermore, "○ + ○ +..." means the total amount of the corresponding components.

[0078] SnO, Bi2O3, TiO2, Fe2O3, and Nb2O5 are negative electrode active material components that serve as sites for absorbing and releasing alkali ions. By incorporating these components, the discharge capacity per unit mass of the negative electrode active material increases, and the charge / discharge efficiency (the ratio of discharge capacity to charge capacity) during the initial charge / discharge cycle tends to improve. However, if the content of these components is too high, the volume change associated with the absorption and release of sodium ions during charge / discharge cycles cannot be alleviated, and cycle characteristics tend to deteriorate. In light of the above, the content range of each component is preferably as follows:

[0079] The SnO content is preferably 0% to 90%, 45% to 85%, 55% to 75%, and particularly preferably 60% to 72%.

[0080] The content of Bi2O3 is preferably 0% to 90%, 10% to 70%, or 15% to 65%, and particularly preferably 25% to 55%.

[0081] The content of TiO2 is preferably 0% to 90%, 5% to 72%, 10% to 68%, 12% to 58%, or 15% to 49%, and particularly preferably 15% to 39%.

[0082] The content of Fe2O3 is preferably 0% to 90%, 15% to 85%, or 20% to 80%, and particularly preferably 25% to 75%.

[0083] The content of Nb2O5 is preferably 0% to 90%, 7% to 79%, 9% to 69%, 11% to 59%, 13% to 49%, and particularly preferably 15% to 39%. The content of SnO+Bi2O3+TiO2+Fe2O3+Nb2O5 is preferably 0% to 90%, 5% to 85%, and particularly preferably 10% to 80%.

[0084] SiO2, BO3, and PO5 are network-forming oxides that surround the sodium ion absorption and desorption sites in the negative electrode active material components, further improving cycle characteristics. In particular, SiO2 and PO5 not only further improve cycle characteristics but also have excellent sodium ion conductivity, which further improves rate characteristics.

[0085] The ratio of SiO2+B2O3+P2O5 is preferably 5% to 85%, 6% to 79%, 7% to 69%, 8% to 59%, or 9% to 49%, and particularly preferably 10% to 39%. If the ratio of SiO2+B2O3+P2O5 is too low, the volume change of the negative electrode active material components accompanying the absorption and release of sodium ions during charge and discharge cannot be alleviated, causing structural destruction and making the cycle characteristics more likely to deteriorate. On the other hand, if the ratio of SiO2+B2O3+P2O5 is too high, the content of the negative electrode active material components will be relatively low, and the charge / discharge capacity per unit mass of the negative electrode active material will tend to be small.

[0086] The preferred ranges of the contents of SiO2, B2O3 and P2O5 are as follows:

[0087] The SiO2 content is preferably 0% to 75%, 5% to 75%, 7% to 60%, 10% to 50%, 12% to 40%, and particularly preferably 20% to 35%. If the SiO2 content is too high, the discharge capacity tends to decrease.

[0088] The P2O5 content is preferably 5% to 75%, 7% to 60%, 10% to 50%, 12% to 40%, and particularly preferably 20% to 35%. If the P2O5 content is too low, it becomes difficult to obtain the above-mentioned effects. On the other hand, if the P2O5 content is too high, the discharge capacity and water resistance tend to decrease. Furthermore, when an aqueous electrode paste is prepared, unwanted heterogeneous crystals are generated, which breaks the P2O5 network, and the cycle characteristics tend to decrease.

[0089] The B2O3 content is preferably 0% to 75%, 5% to 75%, 7% to 60%, 10% to 50%, 12% to 40%, and particularly preferably 20% to 35%. If the B2O3 content is too high, the discharge capacity is likely to decrease and the chemical durability is likely to decrease.

[0090] The negative electrode active material precursor powder is preferably one that, upon firing, forms an amorphous phase together with the negative electrode active material crystals. The formation of the amorphous phase can improve sodium ion conductivity in the negative electrode layer 5 and at the interface between the negative electrode layer 5 and the solid electrolyte layer 4.

[0091] The average particle size of the negative electrode active material precursor powder is preferably 0.01 μm to 15 μm, 0.05 μm to 12 μm, and particularly preferably 0.1 μm to 10 μm. If the average particle size of the negative electrode active material precursor powder is too small, the agglomeration force between the negative electrode active material precursor powder particles will be strong, and dispersibility will tend to be poor when the powder is made into a paste. As a result, the internal resistance of the battery will increase and the operating voltage will tend to decrease. In addition, the electrode density will decrease and the capacity per unit volume of the battery will tend to decrease. On the other hand, if the average particle size of the negative electrode active material precursor powder is too large, sodium ions will be less likely to diffuse and the internal resistance will tend to increase. In addition, the surface smoothness of the electrode will tend to be poor.

[0092] In the present invention, the average particle size means D50 (volume-based average particle size) and indicates a value measured by a laser diffraction scattering method.

[0093] The thickness of the negative electrode layer 5 is preferably in the range of 0.3 μm to 300 μm, and more preferably in the range of 3 μm to 150 μm. If the thickness of the negative electrode layer 5 is too thin, the absolute capacity (mAh) of the negative electrode tends to decrease. If the thickness of the negative electrode layer 5 is too thick, the resistance increases, and the capacity (mAh / g) tends to decrease.

[0094] The negative electrode layer 5 may contain a solid electrolyte powder, a conductive additive, etc. By incorporating a solid electrolyte powder into the negative electrode composite, the contact interface between the negative electrode active material and the solid electrolyte powder increases, facilitating the absorption and release of sodium ions during charge and discharge, thereby further improving the rate characteristics.

[0095] The solid electrolyte powder may be made of the same material as that used for the solid electrolyte layer 4. The solid electrolyte powder preferably has an average particle size of 0.01 μm to 15 μm, 0.05 μm to 10 μm, and particularly preferably 0.1 μm to 5 μm.

[0096] If the average particle size of the solid electrolyte powder is too large, the distance required for sodium ion conduction becomes longer, and sodium ion conductivity tends to decrease. Furthermore, the sodium ion conduction path between the negative electrode active material powder and the solid electrolyte powder tends to decrease. As a result, the discharge capacity tends to decrease. On the other hand, if the average particle size of the solid electrolyte powder is too small, degradation due to elution of sodium ions or reaction with carbon dioxide occurs, and sodium ion conductivity tends to decrease. Furthermore, voids tend to form, which also tends to decrease electrode density. As a result, the discharge capacity tends to decrease.

[0097] The volume ratio of the negative electrode active material precursor powder to the solid electrolyte powder is preferably 20:80 to 95:5, 30:70 to 90:10, and particularly preferably 35:65 to 88:12.

[0098] Examples of the conductive additive include carbon powder. The inclusion of the conductive additive can reduce the internal resistance of the negative electrode layer 5. The conductive additive is preferably contained in the negative electrode layer 5 in an amount of 0 to 20% by mass, and more preferably 1 to 10% by mass.

[0099] <Example> The present invention will be described below based on examples, but the present invention is not limited to these examples.

[0100] Example 1 (1-a) Preparation of solid electrolyte (1-a-1) Preparation of solid electrolyte powder Sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), magnesium oxide (MgO), aluminum oxide (Al2O3), zirconium oxide (ZrO2), and yttrium oxide (Y2O3) were used to prepare raw powders with the following molar composition: Na2O 14.2%, MgO 5.5%, Al2O3 75.4%, ZrO2 4.7%, and Y2O3 0.2%. The raw powders were compacted using a uniaxial press at 40 MPa in a φ20 mm mold and sintered at 1600°C for 30 minutes to obtain β"-alumina. Note that the sintered β"-alumina was handled in an atmosphere with a dew point of -40°C or below.

[0101] The resulting β"-alumina was pulverized using an alumina mortar and pestle and passed through a mesh with 300 μm openings. The passed powder was then pulverized at 300 rpm for 30 minutes (with a 15-minute break every 15 minutes) using a Fritsch Planetary Ball Mill P6 equipped with φ5 mm YTZ (yttria-stabilized zirconia) balls, and further passed through a mesh with 20 μm openings. Subsequently, air classification was performed using an air classifier (Nippon Pneumatic Mfg. Co., Ltd., Model MDS-1) to obtain a solid electrolyte powder consisting of β"-alumina. All operations were carried out in an atmosphere with a dew point of -40°C or lower.

[0102] (1-a-2) Preparation of solid electrolyte layer Sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), magnesium oxide (MgO), aluminum oxide (Al2O3), zirconium oxide (ZrO2), and yttrium oxide (YO3) were mixed to a composition of 14.2% Na2O, 5.5% MgO, 75.4% Al2O3, 4.7% ZrO2, and 0.2% YO3 by mole. The raw powders were then wet-mixed in ethanol for 4 hours. After evaporating the ethanol, an acrylic ester copolymer (Kyoeisha Chemical Co., Ltd., "Orikox 1700") was used as the binder and benzyl butyl phthalate was used as the plasticizer. The raw powder:binder:plasticizer ratio was 83.5:15:1.5 (by mass). The mixture was dispersed in N-methylpyrrolidone and thoroughly stirred in a planetary centrifugal mixer to form a slurry.

[0103] The slurry obtained above was applied onto a PET film using a doctor blade with a gap of 250 μm, and then dried at 70° C. to obtain a green sheet. The obtained green sheet was then pressed at 90° C. and 40 MPa for 5 minutes using an isostatic pressing device.

[0104] The pressed green sheet was fired at 1600°C for 30 minutes to obtain a 12 mm square, 50 μm thick solid electrolyte layer (solid electrolyte sheet) made of β″-alumina. The fired solid electrolyte layer was handled in an atmosphere with a dew point of −40°C or lower.

[0105] (1-b) Preparation of positive electrode active material precursor powder Sodium metaphosphate (NaPO), cobalt oxide (CoO), sodium carbonate (NaCO), and orthophosphoric acid (HPO) were used as raw materials to prepare raw material powder with a composition of 30.3% NaO, 36.3% CoO, and 33.3% PO. The raw material powder was placed in a quartz crucible and melted in air at 1300°C for 90 minutes using an electric furnace. The molten glass was then poured between a pair of rotating rollers and shaped while being rapidly cooled, yielding a film-like glass body with a thickness of 0.1 mm to 2 mm.

[0106] The obtained film-like glass body was ball milled using φ20 mm ZrO2 balls for 5 hours and passed through a resin sieve with 120 μm openings to obtain a coarse glass powder with an average particle size of 3 μm to 15 μm. Next, this coarse glass powder was ball milled using φ3 mm ZrO2 balls and ethanol as a milling aid for 80 hours to obtain a glass powder (positive electrode active material precursor powder) with an average particle size of 0.6 μm.

[0107] (1-c) Preparation of the positive electrode layer (positive electrode composite layer) The positive electrode active material precursor powder was weighed out to 72% by mass, the solid electrolyte powder prepared in (1-a-1) to 25% by mass, and acetylene black to 3% by mass (the volume ratio of the positive electrode active material precursor powder to the solid electrolyte powder was 76:24), and mixed for 2 hours using an agate mortar and pestle. 20 parts by mass of N-methylpyrrolidone (containing 10% by mass of polypropylene carbonate) was added to 100 parts by mass of the resulting mixed powder, and the mixture was thoroughly stirred using a planetary mixer to form a slurry. All of the above operations were carried out in an atmosphere with a dew point of -40°C or below.

[0108] The obtained slurry was applied to the center of one of the main surfaces of the solid electrolyte layer prepared in (1-a-2) in a 10 mm square with a thickness of 50 μm, and dried at 70°C for 3 hours. Next, it was fired in a nitrogen gas atmosphere at 500°C for 30 minutes. As a result, a positive electrode layer was formed on one of the main surfaces of the solid electrolyte layer. In a plan view from the main surface side on which the positive electrode layer of the solid electrolyte layer was formed, the area of ​​the protruding part of the solid electrolyte layer was 30.6% of the area of ​​the solid electrolyte layer. When the obtained positive electrode layer was observed with a transmission electron microscope (TEM), a lattice image corresponding to a crystalline structure was not observed in some regions, confirming the presence of an amorphous phase. In addition, when the powder X-ray diffraction pattern of the material constituting the positive electrode layer was examined, it was found that Na 3.64 Co 2.18 Diffraction lines originating from (P2O7)2 crystals and crystalline diffraction lines originating from each solid electrolyte powder used were confirmed.

[0109] (1-d) Fabrication of all-solid-state sodium-ion secondary battery A first metal film made of Al was formed on the positive electrode layer of the laminate of the solid electrolyte and the positive electrode layer obtained in (1-c) using a sputtering device ("SC-701AT" manufactured by Sanyu Electronics Co., Ltd.) Then, in an argon atmosphere with a dew point of -60°C or lower, a 10 mm square piece of metallic sodium (thickness: 70 μm) that would become the negative electrode layer was pressure-bonded to the center of the main surface of the solid electrolyte opposite the positive electrode layer.

[0110] Two all-solid-state sodium ion secondary batteries were fabricated according to the above steps (1-a) to (1-d).

[0111] (1-e) Fabrication of bipolar all-solid-state sodium ion secondary battery Two all-solid-state sodium ion secondary batteries obtained in (a) to (d) were stacked with a current collector layer (current collector sheet) made of 12 mm square Al foil (thickness: 3 μm) interposed therebetween, placed on the bottom cover of a coin cell, and then covered with an upper cover to produce a CR2032-type test battery. The two all-solid-state sodium ion secondary batteries and current collector layers were stacked so that, in plan view, the current collector layer had a protruding portion that protruded outward from the positive electrode layer and the negative electrode layer. In plan view from the main surface of the current collector layer on which the positive electrode layer was laminated, the area of ​​the protruding portion was 30.6% of the total area of ​​the protruding portion and the current collector layer. In plan view from the main surface of the current collector layer on which the negative electrode layer was laminated, the area of ​​the protruding portion was 30.6% of the total area of ​​the protruding portion and the current collector layer. In this manner, a bipolar all-solid-state sodium ion secondary battery was obtained. FIG. 11 shows a schematic cross-sectional view of the bipolar all-solid-state sodium ion secondary battery of Example 1.

[0112] (Comparative Example 1) As Comparative Example 1, an all-solid-state sodium ion secondary battery was fabricated by the same method as in (1-a) to (1-d) of Example 1, and placed on the bottom lid of a coin cell, and then covered with an upper lid to fabricate a CR2032 type test battery. Note that this was not a bipolar type all-solid-state sodium ion secondary battery.

[0113] (Charge / discharge test) The fabricated evaluation batteries of Example 1 and Comparative Example 1 were subjected to CC (constant current) charging from an open circuit voltage at 30° C. for 10 hours, followed by CC discharging at 30° C. The C rate during charging and discharging was 0.1C.

[0114] 12 is a diagram showing charge / discharge curves of the evaluation battery of Comparative Example 1. FIG. 13 is a diagram showing charge / discharge curves of the evaluation battery of Example 1.

[0115] As shown in Figure 12, the voltage obtained in the evaluation battery of Comparative Example 1 is 4.3 V. In contrast, as shown in Figure 13, the voltage obtained in the evaluation battery of Example 1 is 8.4 V. Thus, it can be seen that a high voltage can be obtained in Example 1.

[0116] Example 2 (2-a) Preparation of solid electrolyte (2-a-1) Preparation of solid electrolyte powder In the same manner as in Example 1, a solid electrolyte powder made of β″-alumina was prepared.

[0117] (2-a-2) Preparation of solid electrolyte layer A solid electrolyte layer (solid electrolyte sheet) made of β″-alumina was produced in the same manner as in Example 1. In this example, the solid electrolyte layer was produced so as to have a size of 11 mm square and a thickness of 50 μm.

[0118] (2-b) Preparation of positive electrode active material precursor powder Sodium metaphosphate (NaPO), iron (III) oxide (FeO), sodium carbonate (NaCO), and orthophosphoric acid (HPO) were used as raw materials to prepare raw material powders with a composition of 40% NaO, 20% FeO, and 40% P0 in mole percent. The raw material powders were placed in a platinum crucible and melted in an electric furnace at 1300°C for 90 minutes in the atmosphere. The molten glass was then poured between a pair of rotating rollers and shaped while being rapidly cooled, yielding a film-like glass body with a thickness of 0.1 mm to 2 mm.

[0119] The obtained film-like glass body was ball-milled for 5 hours using φ20 mm ZrO2 balls and passed through a resin sieve with 120 μm mesh to obtain a coarse glass powder with an average particle size of 18 μm. This coarse glass powder was then ball-milled for 80 hours using φ3 mm ZrO2 balls and ethanol as a grinding aid to obtain a glass powder (positive electrode active material precursor powder) with an average particle size of 0.6 μm.

[0120] (2-c) Preparation of the positive electrode layer (positive electrode composite layer) The mixture consisted of 72% cathode active material precursor powder, 25% solid electrolyte powder prepared in (2-a-1), and 3% acetylene black (volume ratio of cathode active material precursor powder to solid electrolyte powder: 76:24) and mixed for 2 hours using an agate mortar and pestle. 20 parts by mass of N-methylpyrrolidone (containing 10% by mass of polypropylene carbonate) was added to 100 parts by mass of the resulting mixed powder, and the mixture was thoroughly stirred using a planetary mixer to form a slurry. All of the above operations were carried out in an atmosphere with a dew point of -40°C or below.

[0121] The resulting slurry was applied to the center of one main surface of the solid electrolyte layer prepared in (2-a-2) in a 10 mm square, 70 μm thick area and dried at 70°C for 3 hours. It was then fired at 530°C for 60 minutes in a 4 vol% H2 / 96 vol% N2 mixed gas atmosphere. This resulted in a positive electrode layer being formed on one main surface of the solid electrolyte layer. In a planar view of the main surface on which the positive electrode layer was formed, the area of ​​the protruding portion of the solid electrolyte layer was 17.4% of the area of ​​the solid electrolyte layer. Observation of the resulting positive electrode layer using a transmission electron microscope (TEM) revealed that in some regions, no lattice image corresponding to the crystalline structure was observed, confirming the presence of an amorphous phase. Furthermore, powder X-ray diffraction patterns of the materials constituting the positive electrode composite layer revealed diffraction lines originating from Na2FeP2O7 crystals and crystalline diffraction lines originating from each solid electrolyte powder used.

[0122] (2-d) Fabrication of all-solid-state sodium-ion secondary battery A first metal film made of Al was formed on the positive electrode layer of the laminate of the solid electrolyte and the positive electrode layer obtained in (2-c) using a sputtering device ("SC-701AT" manufactured by Sanyu Electronics Co., Ltd.). Thereafter, in an argon atmosphere with a dew point of -60°C or less, a 10 mm square piece of metallic sodium (thickness: 70 μm) that would become the negative electrode layer was pressure-bonded to the center of the main surface of the solid electrolyte opposite the positive electrode layer. Two all-solid-state sodium ion secondary batteries were fabricated using the above (2-a) to (2-d).

[0123] (2-e) Fabrication of bipolar all-solid-state sodium ion secondary battery Two all-solid-state sodium ion secondary batteries obtained in (2-a) to (2-d) above were stacked via a current collector layer (current collector sheet) made of 10.5 mm square Al foil (thickness: 3 μm). The stack was placed on the bottom lid of a coin cell, and then the top lid was placed on top to produce a CR2032-type test battery. The two all-solid-state sodium ion secondary batteries and current collector layers were stacked so that, in plan view, the current collector layer had a protruding portion that protruded outward from the positive electrode layer and the negative electrode layer. When viewed from the main surface of the current collector layer on which the positive electrode layer was laminated, the area of ​​the protruding portion was 9.3% of the total area of ​​the protruding portion and the current collector layer. When viewed from the main surface of the current collector layer on which the negative electrode layer was laminated, the area of ​​the protruding portion was 9.3% of the total area of ​​the protruding portion and the current collector layer. A bipolar all-solid-state sodium ion secondary battery was thus obtained.

[0124] Example 3 Three all-solid-state sodium ion secondary batteries were fabricated using the same method as in Example 2. A stack was fabricated by stacking three all-solid-state sodium ion secondary batteries with a current collector layer (current collector sheet) made of 10.5 mm square Al foil (thickness: 3 μm) interposed between adjacent all-solid-state sodium ion secondary batteries. The stack was placed on the bottom lid of a coin cell, and then the top lid was placed on top to fabricate a CR2032 test battery. The three all-solid-state sodium ion secondary batteries and current collector layers were stacked so that, in plan view, the current collector layer had a protruding portion that protruded outward from the positive electrode layer and the negative electrode layer. In plan view from the main surface of the current collector layer on which the positive electrode layer was laminated, the area of ​​the protruding portion was 9.3% of the total area of ​​the protruding portion and the current collector layer. In plan view from the main surface of the current collector layer on which the negative electrode layer was laminated, the area of ​​the protruding portion was 9.3% of the total area of ​​the protruding portion and the current collector layer. In plan view from the main surface of the current collector layer on which the negative electrode layer was laminated, the area of ​​the protruding portion was 9.3% of the total area of ​​the protruding portion and the current collector layer. In this way, a bipolar type all-solid-state sodium ion secondary battery was obtained.

[0125] (Comparative Example 2) As a comparative example, an all-solid-state sodium ion secondary battery was fabricated by the same method as in (2-a) to (2-d) of Example 2, and placed on the bottom lid of a coin cell, and then covered with an upper lid to fabricate a CR2032 type test battery. Note that this was not a bipolar type all-solid-state sodium ion secondary battery.

[0126] (Charge / discharge test) The evaluation batteries prepared in Examples 2, 3, and Comparative Example 2 were subjected to CC (constant current) charging from an open circuit voltage at 60° C. for 100 hours, followed by CC discharging at 60° C. The C rate during charging and discharging was 0.01C.

[0127] 14 is a diagram showing charge / discharge curves of the evaluation batteries of Example 2, Example 3, and Comparative Example 2. In Fig. 14, the solid line shows the results of Example 2, the two-dot chain line shows the results of Example 3, and the dashed line shows the results of Comparative Example 2.

[0128] 14, the voltage obtained in the evaluation battery of Comparative Example 2 is 2.8 V. In contrast, the voltage obtained in the evaluation battery of Example 2 is 5.7 V, and the voltage obtained in the evaluation battery of Example 3 is 8.3 V. Thus, it can be seen that high voltages can be obtained in Examples 2 and 3.

[0129] Example 4 (4-a) Preparation of solid electrolyte A solid electrolyte powder and a solid electrolyte layer were prepared in the same manner as in Example 2 (2-a).

[0130] (4-b) Preparation of positive electrode active material precursor powder A positive electrode active material precursor powder was produced in the same manner as in (2-b) of Example 2, except that sodium metaphosphate (NaPO), nickel oxide (NiO), sodium carbonate (NaCO), and orthophosphoric acid (HPO) were used as raw materials to prepare a raw material powder having a composition, in mole percent, of 30.3% NaO, 36.4% NiO, and 33.3% PO.

[0131] (4-c) Preparation of the positive electrode layer (positive electrode composite layer) A positive electrode layer was formed on one main surface of the solid electrolyte layer in the same manner as in (2-c) of Example 2, using the solid electrolyte powder and solid electrolyte layer obtained in (4-a) and the positive electrode active material precursor powder obtained in (4-b). The procedure was the same as in (2-c) of Example 2, except that the firing conditions were set to 625°C for 30 minutes in an N2 gas atmosphere. Observation of the resulting positive electrode layer using a transmission electron microscope (TEM) revealed that no lattice image corresponding to a crystalline structure was observed in some regions, confirming the presence of an amorphous phase. Furthermore, powder X-ray diffraction patterns of the materials constituting the positive electrode composite layer revealed Na 3.64 Ni 2.18 Diffraction lines originating from (P2O7)2 crystals and crystalline diffraction lines originating from the solid electrolyte powder used were confirmed.

[0132] (4-d) Fabrication of all-solid-state sodium-ion secondary battery Two all-solid-state sodium ion secondary batteries were fabricated in the same manner as in Example 2 (2-d).

[0133] (4-e) Fabrication of bipolar all-solid-state sodium ion secondary battery A bipolar type all-solid-state sodium ion secondary battery was fabricated in the same manner as in Example 2 (2-e).

[0134] (Comparative Example 3) As a comparative example, an all-solid-state sodium ion secondary battery was fabricated by the same method as in (4-a) to (4-d) of Example 4, and placed on the bottom lid of a coin cell, and then covered with an upper lid to fabricate a CR2032 type test battery. Note that this was not a bipolar type all-solid-state sodium ion secondary battery.

[0135] (Charge / discharge test) The evaluation batteries prepared in Example 4 and Comparative Example 3 were subjected to CC (constant current) charging from an open circuit voltage at 60°C for 100 hours. Then, CC discharging was performed at 60°C. The C rate during charging and discharging was 0.01C. The end-of-charge voltage for Example 4 was 10.4V and the end-of-discharge voltage was 4V, while the end-of-charge voltage for Comparative Example 3 was 5.2V and the end-of-discharge voltage was 2V.

[0136] In the evaluation battery of Comparative Example 3, the resulting discharge voltage was 4.7 V and the discharge capacity was 51 mAh / g. In contrast, in the evaluation battery of Example 4, the resulting discharge voltage was 9.4 V and the discharge capacity was 50 mAh / g. Thus, it can be seen that a high voltage can be obtained in Example 4. [Explanation of symbols]

[0137] 1...All-solid-state sodium-ion secondary battery 2...Current collector layer 2a...first principal surface 2b...Second main surface 3...Positive electrode layer 4...Solid electrolyte layer 4a...Third principal surface 4b...Fourth main surface 5...Anode layer 6...Protruding part 7...First metal film 8...Second metal film 9...Solid electrolyte layer protrusion 10...Bipolar all-solid-state sodium-ion secondary battery 27...First metal film 28...Second metal film 34...Solid electrolyte layer 39...Solid electrolyte layer protrusion 44...Solid electrolyte layer 54...Solid electrolyte layer 56...Protrusion 59...Solid electrolyte layer protrusion 66...Protrusion

Claims

1. a plurality of all-solid-state sodium ion secondary batteries, each including a positive electrode layer capable of absorbing and releasing sodium, a solid electrolyte layer made of a sodium ion conductive oxide, and a negative electrode layer capable of absorbing and releasing sodium, stacked in this order; a current collector layer provided between the positive electrode layer of the all-solid-state sodium ion secondary battery and the negative electrode layer of another all-solid-state sodium ion secondary battery, the current collector layer being shared by the positive electrode layer and the negative electrode layer; a protruding portion is provided which is connected to an outer peripheral edge of the current collector layer and protrudes outward beyond an outer peripheral edge of the positive electrode layer and / or the negative electrode layer in a plan view, The thickness of the protrusion is 0.1 μm or more and 15 μm or less, The bipolar type all-solid-state sodium ion secondary battery, wherein the protrusion is formed from a material different from that of the current collector layer.

2. a plurality of all-solid-state sodium ion secondary batteries, each including a positive electrode layer capable of absorbing and releasing sodium, a solid electrolyte layer made of a sodium ion conductive oxide, and a negative electrode layer capable of absorbing and releasing sodium, stacked in this order; a current collector layer provided between the positive electrode layer of the all-solid-state sodium ion secondary battery and the negative electrode layer of another all-solid-state sodium ion secondary battery, the current collector layer being shared by the positive electrode layer and the negative electrode layer; a protruding portion is provided which is connected to an outer peripheral edge of the current collector layer and protrudes outward beyond an outer peripheral edge of the positive electrode layer and / or the negative electrode layer in a plan view, an area of ​​the protrusion is 1% or more and 50% or less of a total area of ​​the protrusion and the current collector layer in a plan view; The bipolar type all-solid-state sodium ion secondary battery, wherein the protrusion is formed from a material different from that of the current collector layer.

3. 3. The bipolar type all-solid-state sodium ion secondary battery according to claim 1, wherein the solid electrolyte layer has a portion that protrudes outward from an outer periphery of the positive electrode layer and / or the negative electrode layer in a plan view.

4. 4. The bipolar type all-solid-state sodium ion secondary battery according to claim 3, wherein an area of ​​a portion of the solid electrolyte layer protruding outward from an outer peripheral edge of the positive electrode layer and / or the negative electrode layer in a plan view is 1% or more and 50% or less of an area of ​​the solid electrolyte layer.

5. a plurality of all-solid-state sodium ion secondary batteries, each including a positive electrode layer capable of absorbing and releasing sodium, a solid electrolyte layer made of a sodium ion conductive oxide, and a negative electrode layer capable of absorbing and releasing sodium, stacked in this order; a current collector layer provided between the positive electrode layer of the all-solid-state sodium ion secondary battery and the negative electrode layer of another all-solid-state sodium ion secondary battery, the current collector layer being shared by the positive electrode layer and the negative electrode layer; the solid electrolyte layer has a portion that protrudes outward from an outer periphery of the positive electrode layer and / or the negative electrode layer in a plan view, an area of ​​a portion of the solid electrolyte layer protruding outward from an outer circumferential edge of the positive electrode layer and / or the negative electrode layer is 1% or more and 50% or less of an area of ​​the solid electrolyte layer, in a plan view; The solid electrolyte layer does not cover the side surfaces of the positive electrode layer and the negative electrode layer.

6. The bipolar type all-solid-state sodium ion secondary battery according to any one of claims 1 to 5, wherein the current collector layer is made of at least one selected from the group consisting of aluminum, titanium, silver, copper, stainless steel, alloys containing these metals, and graphite.

7. The bipolar type all-solid-state sodium ion secondary battery according to any one of claims 1 to 6, wherein the solid electrolyte layer contains at least one of β-alumina, β″-alumina, and NASICON type crystals.

Citation Information

Patent Citations

  • Multipole shielded electric connector

    JP2002075544A

  • Method for manufacturing lithium polymer battery and battery obtained by the same

    JP2006173000A

  • Solid electrolyte composition, sheet for all-solid type secondary battery, all-solid type secondary battery, and methods for manufacturing sheet for all-solid type secondary battery and all-solid type secondary battery

    JP2017147173A

  • Method of producing alkali metal or alkali-ion batteries having high volumetric and gravimetric energy densities

    US20170207489A1

  • Bipolar all-solid-state battery

    WO2012164642A1